THE EFFECT OF p-HIDROXY m-METHOXY CHALCONE (pHmMK) ON Bcl-2 AND Bax PROTEIN EXPRESSION IN MCF-7 BREAST CANCER CELL LINES - Arianingrum, Retno (Jurnal Penelitian Saintek, 2017)
Chalcone derivate compound [3-(4’-hydroxy-3’-methoxyphenyl) -1-phenyl-2- propene-1-on)] or para hydroxyl meta methoxy chalcone (pHmMC) has been observed. It showed that it is able to induce apoptosis (cell death) in MCF-7 breast cancer cell. This study was aimed at ï¬ nding out the apoptosis mechanism pathway of pHmMC on MCF-7 cells by observing its effect on Bcl-2 and Bax proteins. The protein expression was observed by using immunocytochemistry (ICC) and analyzed using ImageJ software. The results showed that the pHmMC induce apoptosis through mechanism that decrease expression of Bcl-2 and increase expresion of Bax proteins.